Sinergi kebijakan pajak, retribusi dan aset daerah unggulan untuk peningkatan pendapatan asli daerah di Kabupaten Bungo - Yuvanda, Sesraria; Rachmad R, Muhamamd; Aisyah Rj Nur, Deby (Jurnal Paradigma Ekonomika, 2025)
This study aims to formulate efforts to increase Local Own-Source Revenue (PAD) through the utilization of potential local taxes and levies, as well as the optimization of regional assets. The analytical model used is descriptive qualitative analysis with an in-depth approach. The findings indicate that to enhance PAD, key local taxes that can be optimized include Electricity Tax (PPJ), Land and Building Rights Acquisition Fee (BPHTB), Restaurant Tax, Land and Building Tax (PBB), and Hotel Tax. Priority regional levies include waste management, market services, health services, parking fees, and local business production services. The utilization of regional assets can be carried out through the rental of buildings, land, and heavy equipment. Policies to increase PAD can be implemented through the regulation of tariff settings and procedures for collecting taxes, levies, and the use of regional assets via regional regulations